Integrated behavior and transcriptomic analysis provide valuable insights into the response mechanisms of Dastarcus helophoroides Fairmaire to light exposure - Jiang, Xianglan; Li, Tengfei; Hai, Xiaoxia; Zheng, Xiang; Wang, Zhigang; Lyu, Fei (Frontiers in Physiology, 2023)
Light traps have been widely used to monitor and manage pest populations, but natural enemies are also influenced. The Dastarcus helophoroides Fairmaire is an important species of natural enemy for longhorn beetles. However, the molecular mechanism of D. helophoroides in response to light exposure is still scarce. Here, integrated behavioral, comparative transcriptome and weighted gene co-expression network analyses were applied to investigate gene expression profiles in the head of D. helophoroides at different light exposure time. The results showed that the phototactic response rates of adults were 1.67%-22.5% and females and males displayed a negative phototaxis under different light exposure (6.31 × 10 18 (photos/m 2 /s)); the trapping rates of female and male were influenced significantly by light exposure time, diel rhythm, and light wavelength in the behavioral data. Furthermore, transcriptome data showed that a total of 1 052 significantly differentially expressed genes (DEGs) were identified under different light exposure times relative to dark adaptation. Bioinformatics analyses revealed that the "ECM-receptor interaction", "focal adhesion", "PI3K-Akt signaling" and "lysosome" pathways were significantly downregulated with increasing light exposure time. Furthermore, nine DEGs were identified as hub genes using WGCNA analysis. The results revealed molecular mechanism in negative phototactic behavior response of D. helophoroides under the light exposure with relative high intensity, and provided valuable insights into the underlying molecular response mechanism of nocturnal beetles to light stress.